Conserving genes and genotypes of trees - Kärkkäinen, Katri (MTT, 2008)
Conservation of genes and genotypes in trees is important e.g. for maintaining genetic biodiversity, for tree breeding, and for preserving valuable material for research. Viability of tree populations in future is dependent on genetic variation enabling to adapt to changing environment. The difficult task in conservation genetics is to identify most suitable populations and genotypes for conservation. Recent progress e.g., in methods and knowledge on the genetic basis of adaptive variation will help to improve conservation plans. In tree breeding and in basic research, preservation of valuable genotypes is needed. Use of different methods for preserving genetic variation and genotypes situ and ex situ (e.g. cryopreservation) will be discussed.
Keywords: Ka; biodiversity; tree breeding